Nonuniform but highly preferential stemflow routing along bark surfaces and actual smaller infiltration areas than previously assumed: A case study on European beech (Fagus sylvatica L.) and sycamore maple (Acer pseudoplatanus L.). Issue 6 (30th June 2020) - Tischer, Alexander; Michalzik, Beate; Lotze, Robert
Abstract: Canopy and tree morphology are assumed to play a significant role in modulating the amount of rainfall water during its routing throughout the vegetation and the near‐surface Critical Zone. One crucial point of research addresses the spatial extent of stemflow (SF) infiltration, because its concentration over small areas at the trunk base appears to affect the magnitude and timing of water and solutes input to the soil and hence amplify biogeochemical cycling. By a Brilliant Blue tracer experiment, we examined the flow patterns of SF water along the trunk surface of two broadleaved tree species ( Fagus sylvatica and Acer pseudoplatanus ) and the infiltration area at the trunk base and down to 0.12‐m soil depth following natural rainfall events. Our results point to highly preferential SF with smaller washed‐off stem areas for sycamore maple (≤15%) compared with European beech (≤39%). The infiltration area is remarkably smaller than the basal area (BA), accounting for only 17% of the BA for beech and for 30% for maple. Differences in decolourized stem areas between the trees do not relate to the magnitude of infiltration areas at the soil surface, suggesting a strong effect of coarse root abundance and run‐off properties on the funnelling of SF water. In essence, our investigation exhibited that SF routing along bark surfaces and infiltration at the trunk base were spatially more concentrated than commonly assumed. The outcome of this study might contribute to our understanding on hydrological and biogeochemical interlinkages between the plant cover and the near‐surface Critical Zone.